2021
DOI: 10.1155/2021/6690095
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship of Bone Turnover Markers and Bone Mineral Density in Community-Dwelling Postmenopausal Women

Abstract: Aims. To explore the relationships of procollagen type 1 N-terminal propeptide (P1NP) and β cross-linked C-telopeptide of type 1 collagen (β-CTX) with bone mineral density (BMD) in postmenopausal women. Methods. All postmenopausal women were selected from a community-based case-control study. The anteroposterior L1-L4 and left proximal femur BMD were measured. P1NP and β-CTX were also collected and tested. The main correlation analysis was applied to explore the relationships of BMD, P1NP, and β-CTX. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Bon| turnover markers (BTMs) are a group of metabolites or enzymes which are released by osteoblasts or osteoclasts during the bone remodeling process. BTMs could provide a dynamic picture of changes in bone remodeling, and thus identify changes in the bone remodeling within a relatively short time interval ( 15 ). BTMs are independent predictors of fracture risk and future bone loss ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bon| turnover markers (BTMs) are a group of metabolites or enzymes which are released by osteoblasts or osteoclasts during the bone remodeling process. BTMs could provide a dynamic picture of changes in bone remodeling, and thus identify changes in the bone remodeling within a relatively short time interval ( 15 ). BTMs are independent predictors of fracture risk and future bone loss ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bone resorption and bone formation are collectively known as bone turnover, which allows for the removal and replacement of old and damaged bone, thus maintaining bone strength [51]. Former studies have shown that markers of bone resorption and bone formation may present with high concentrations during puberty [52,53]. In the results of the binary logistic regression analysis in this study, these ve markers did not differ signi cantly between the two groups.…”
Section: P Valuesmentioning
confidence: 39%
“…ALP, N-MID, and β-CTX are markers of bone formation and resorption, which can be easily detected and directly reflect the change in bone metabolism before bone morphological change ( 14 , 21 ). β-CTX is a C-terminal cross-linked peptide of type I collagen, which is produced in the process of collagen decomposition and can be used to indirectly reflect the function and activity of osteoclasts in the skeletal system ( 22 ). β-CTX was stable for 8 h at room temperature and 48 h at 4°C in serum ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…β-CTX was stable for 8 h at room temperature and 48 h at 4°C in serum ( 23 ). It could be considered an ideal and stable marker to reflect bone resorption ( 22 ). N-MID is the hydrolytic fragment of osteocalcin secreted by osteoblasts and can be used to reflect the process of bone formation.…”
Section: Discussionmentioning
confidence: 99%